Effect of animal manure, crop type, climate zone, and soil attributes on greenhouse gas emissions from agricultural soils—A global meta-analysis. (1st January 2021) - Shakoor, Awais; Shakoor, Saba; Rehman, Abdul; Ashraf, Fatima; Abdullah, Muhammad; Shahzad, Sher Muhammad; Farooq, Taimoor Hassan; Ashraf, Muhammad; Manzoor, Muhammad Aamir; Altaf, Muhammad Mohsin; Altaf, Muhammad Ahsan
Abstract: Agricultural lands, because of their large area and exhaustive management practices, have a substantial impact on the earth's carbon and nitrogen cycles, and agricultural activities consequence in discharges of greenhouse gases (GHGs). Globally, greenhouse gases (GHGs) emissions especially carbon dioxide (CO2 ), methane (CH4 ) and nitrous oxide (N2 O) from the agricultural sector are increasing due to anthropogenic activities. Although, the application of animal manure to the agricultural soil as an organic fertilizer not only improves soil health and agricultural production but also has a significant impact on GHGs emissions. But the extent of GHGs emissions in response to manure application under diverse environmental conditions is still uncertain. Here, a meta-analysis study was conducted using field data (48 peer-reviewed publications) published from 1989 to 2019. Meta-analysis results showed that poultry manure considerably increased CO2, CH4, and N2 O emissions than pig and cattle manure. Furthermore, application of poultry manure also increased ( l n R R ¯ = 0.141, 95% CI = 0.526–0.356) GWP (global warming potential) of total soil GHGs emissions. While, the significant effects on CO2, CH4, and N2 O emissions also occurred at manure rate >320 kg N ha −1 and >60% water filled pore space. The maximum concentrations of CO2, CH4, and N2 O emissions were observed in neutral soils ( l n R R ¯ = 3.375, 95% CI = 3.323–3.428), alkaline soils ( l n R R ¯ = 1.468, 95% CI = 1.403–1.532), and acidic soils ( l n R R ¯ = 2.355, 95% CI = 2.390–2.400), respectively. Soil texture, climate zone and crop type were also found significant factors to increase GHGs emissions. Thus, this meta-analysis revealed a knowledge gap concerning the consequences of animal manure application and rate, climate zone, and physicochemical properties of soil on GHGs emissions from agricultural soils. Highlights: Manure application, particularly poultry manure significantly increased GHGs emissions from croplands. Forty-eight publications were used to conduct a global meta-analysis study. Overall, manure application had no effect on GWP because confidence interval overlapped with zero. Soil physiochemical properties had a strong impact on the response of GHGs emissions to manure application.